2019
DOI: 10.1109/access.2019.2908489
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Meta-Heuristic Optimization Algorithms for 0 – 1 Knapsack Problem: Some Initial Results

Abstract: In this paper, we present some initial results of several meta-heuristic optimization algorithms, namely, genetic algorithms, simulated annealing, branch and bound, dynamic programming, greedy search algorithm, and a hybrid genetic algorithm-simulated annealing for solving the 0-1 knapsack problems. Each algorithm is designed in such a way that it penalizes infeasible solutions and optimizes the feasible solution. The experiments are carried out using both low-dimensional and high-dimensional knapsack problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…In [42], the authors tested the hybridized Genetic Algorithm and Simulated Annealing (IGASA) to get rid of the limitations of GA and SA. The hybrid algorithm (IGASA) has been used for solving both low-dimensional and high-dimensional knapsack problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [42], the authors tested the hybridized Genetic Algorithm and Simulated Annealing (IGASA) to get rid of the limitations of GA and SA. The hybrid algorithm (IGASA) has been used for solving both low-dimensional and high-dimensional knapsack problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More so, these proportions describe what should be the state of blood stocked in the bank in an ideal situation. Relating the population of the donor types to the amount of each blood type available expressed by equations (39)(40)(41)(42)(43)(44)(45)(46), the following equations are obtained:…”
Section: B the Dynamic Mass Balance Systemmentioning
confidence: 99%
“…The hybrid optimization algorithm proposed in this paper consists of three well-known global metaheuristics, namely SOS, GA, and PSO. Further, these three algorithms have been proven to be highly effective, efficient, and robust in solving very complex global optimization problems [41]. Of note is the aforementioned individual algorithms, each having been previously used separately to solve the blood assignment problem, with their respective performance studies having been reported in [10], [26], [31].…”
Section: E Symbiotic Organism Search Genetic Particle Swarm Optimizamentioning
confidence: 99%
See 1 more Smart Citation
“…In [11] and [12] the authors have evaluated the performance of various selection techniques. In [15] the authors evaluated various algorithmic techniques used in optimization of 0/1 knapsack.…”
Section: Background and Related Workmentioning
confidence: 99%